The encouragement and study of improved public management: the Institute of Public Administration of Canada innovative management award - Borins, Sandford F
In the last decade, there has been an international trend to recognize and stimulate managerial execellence. One aspect of the trend has involved researchers writing about wish-performing well-managed organizations. A second aspect has been competitions in Managerial excellence which have used the promise of recognition to encourge such organisations to identify themselves. In 1990, Institute of Public Administration of Canada (IPAC) with the support of the management consultant firm of COopers and Lybrand, held the first annual competition for the IPAC Award for Innovative Management. This article describes the nature of the competition, discusses its benefits for the Public sector, and then analyse the
Keywords: Public Administration - Canada